TAGUCHI EXPERIMENTAL STUDY: THE EFFECT OF BAY LEAF EXTRACT WEIGHT PERCENTAGE AND SAMPLE SIZE ON THE CHARACTERISTICS OF POLYVINYL ALCOHOL FILMS - Hery Sunarsono; Hairul Abral; Adjar Pratoto; Elisabeth Feberlian Gulo; Melbi Mahardika; Mat Uzir Wahit; Vitri Aprila Handayani (Analit : Analytical and Environmental Chemistry, 2025)
This research aims to determine the optimum parameters for incorporating Indonesian bay leaf extract (DS) into a polyvinyl alcohol (PVA) matrix to form a new polymer, PVA/DS. Taguchi's experimental method was employed to obtain the anti-UV properties and optimal mechanical characteristics of the PVA/DS polymer. Factors studied include DS concentration and sample size. The experimental design was prepared using an orthogonal array L16. The ability to block UV radiation (anti-UV) and the mechanical properties of polymer films are determined using UV Vis spectra and tensile testing (ASTM D638). The results of the Signal-to-Noise Ratio analysis show that the DS concentration factor is the most dominant variable in the anti-UV response, with a DS concentration influence factor (delta) value of 72.261, compared to a sample thickness of 1.605. Likewise, for elongation at break, the delta value of DS concentration is 2.43, which is higher than the cross-sectional area of 1.31. Meanwhile, for the tensile strength performance, neither factor was significant; however, the cross-sectional area factor was more dominant than the DS concentration, with a cross-sectional area delta value of 3.29, which is higher than the DS concentration of 2.77. The addition of DS concentration to the anti-UV response is able to block 100% of UV rays compared to PVA, which is only 16%. Meanwhile, for tensile strength, there was a 50.98% increase. The tensile strength of PVA/DS1 reached 75.67 MPa compared to PVA, which was only 50.12 MPa. Meanwhile, elongation at break increased by 14.71% in PVA/DS0.5 (304.43%) compared to PVA (265.40%). Thus, this research successfully applied the Taguchi method to identify the optimum factor combination with a minimum number of experiments. PVA/DS1 film (1% DS) is a film with optimum conditions that can provide superior performance, making it an alternative to conventional plastics that do not decompose easily